2012
DOI: 10.1002/jcu.21890
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of fetal cardiac rhabdomyomas in two successive pregnancies in a woman with tuberous sclerosis

Abstract: Rhabdomyoma is the most common prenatally diagnosed cardiac tumor. We present two cases of fetal cardiac rhabdomyoma. In each case, fetal ultrasound assessment revealed the intracardiac tumors that were confirmed on postnatal imaging. The mother and her previous child were examined for the markers of tuberous sclerosis and diagnosis of tuberous sclerosis was confirmed. Two years later, cardiac rhabdomyomas were again diagnosed in her subsequent pregnancy. In the postpartum period, total regression of the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Fetal cardiac rhabdomyoma is the most common cardiac tumor in fetuses, with an extremely low reported incidence rate in fetal echocardiograms (0.17%) and accounting for 60–86% of primary fetal cardiac tumors. Currently, fetal echocardiography is the primary tool for the early detection of primary cardiac rhabdomyoma ( 4 ). However, in the present case, only right atrial wall thickening was observed, as the tumor was not noticeable in traditional 2D imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal cardiac rhabdomyoma is the most common cardiac tumor in fetuses, with an extremely low reported incidence rate in fetal echocardiograms (0.17%) and accounting for 60–86% of primary fetal cardiac tumors. Currently, fetal echocardiography is the primary tool for the early detection of primary cardiac rhabdomyoma ( 4 ). However, in the present case, only right atrial wall thickening was observed, as the tumor was not noticeable in traditional 2D imaging.…”
Section: Discussionmentioning
confidence: 99%
“… 3 These tumors are diagnosed via ultrasound during the second and third trimester, correlating with TSC in 70%–90% of the cases. 3 , 4 …”
mentioning
confidence: 99%